1997
DOI: 10.1074/jbc.272.7.4412
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Severely Decreased Hydrophobicity in a Subdomain 3/4 Loop on the Dynamics and Stability of Yeast G-actin

Abstract: The hydrophobicity of the subdomain 3/4 hydrophobic loop (262-274) has been implicated to be essential for actin's function. We previously showed (Kuang, B., and Rubenstein, P. A. (1997) J. Biol. Chem. 272, 1237-1247) that a mutant yeast actin (V266G/L267G) with markedly decreased hydrophobicity in this loop conferred severe cold sensitivity to its polymerization. Here we further tested the mutational effect on the conformation and function of G-actin. This GG mutation caused no significant changes in overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…The original Holmes model for F-actin involved a postulated ''hydrophobic plug'' between the two strands, with a loop (residues 263-274) that swung out from the body of the monomer to make a contact with subunits on the opposing strand (20). Subsequent experiments have partially supported this model (21)(22)(23), and it has been shown that locking this loop to the body of the actin subunit by engineered disulfide bonds can prevent normal polymerization (16). We have used the yeast actin triple mutant (L180C͞L269C͞C374A), which places two cysteine residues in positions allowing for the loop to be locked to the body of actin and eliminates the reactive cysteine at position 374 (16).…”
Section: Resultsmentioning
confidence: 86%
“…The original Holmes model for F-actin involved a postulated ''hydrophobic plug'' between the two strands, with a loop (residues 263-274) that swung out from the body of the monomer to make a contact with subunits on the opposing strand (20). Subsequent experiments have partially supported this model (21)(22)(23), and it has been shown that locking this loop to the body of the actin subunit by engineered disulfide bonds can prevent normal polymerization (16). We have used the yeast actin triple mutant (L180C͞L269C͞C374A), which places two cysteine residues in positions allowing for the loop to be locked to the body of actin and eliminates the reactive cysteine at position 374 (16).…”
Section: Resultsmentioning
confidence: 86%
“…Pertinent to this proposition is the recognition that in yeast mitochondrial integrity depends on a carefully regulated fission/fusion cycle which, when interrupted, can result in mitochondrial abnormalities and a loss of mtDNA (43). Hill et al (22) showed that one of the alanine scanning mutants, act1-101, had both a mitochondrial and a vacuolar inheritance phenotype (42). We have recently observed that in this cell the vacuole is also hypervesiculated (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, an assessment of vacuole integrity and inheritance was not part of the characterization of the alaninescanning actin mutants. However, other studies revealed, using yeast actin mutations generated by us (22,42), that actin was involved in both vacuole morphology determination and vacuole inheritance and that mutations could be found that affected vacuole behavior independent of mitochondria (41).…”
Section: Discussionmentioning
confidence: 99%
“…WT yeast actin (a generous gift from P. Rubenstein, University of Iowa, Iowa City) was purified by a DNase I affinity chromatography protocol as described (31,32). F-actin sedimentation assays were performed as described (33).…”
Section: Methodsmentioning
confidence: 99%